Surgical Management of Preputial Prolapse in Crossbred Bulls: A Report of Five Cases - Kumar, Ankush; Rohilla, Shivani (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Due to pendulous and longer sheaths and excessive preputial skin, certain breeds especially those of the Bos indicus or Bos indicus cross bulls are prone to prolapse of the prepuce, thus rendering it susceptible to injury or irritation. Prolapse of the prepuce is characterized by the inner lining of its sheath protruding and everting outward, without showing any inclination to retract (Arthur et al., 1996). Small preputial abrasions lead to formation of swelling and edema which in turn exaggerate further preputial prolapse and hence create a vicious cycle, which may worsen the condition and lead to prolapse of additional lengths of prepuce, its trauma or mutilation combined with desiccation of the exposed tissues leading to necrosis (Maxwell and Edmondson, 2009). Preputial prolapses are classified in four categories as per the severity of edema and injury (Prado and Morgan, 2002). The present paper reports category III to IV preputial prolapse which were successfully managed with surgical intervention in five crossbred bulls.